The sundowners - Templeton, George, 1907-; Le May, Alan, 1899-1964; Preston, Robert, 1918-1987; Le May, Alan, 1899-1964.; Le May-Templeton Pictures; Cinetel Films ([Los Angeles, CA] : Le May-Templeton Pictures, 1950)
When two brothers find their ranch empire threatened, their gun-slinging brother comes back home to help.
Originally released as a motion picture in 1950.
Based on the story "Thunder in the dust" by Alan Le May.
Robert Preston, Robert Sterling, Chill Wills, Cathy Downs, John Litel, John Barrymore, Jr.
Cinematographer, Winton C. Hoch; editor, Jack Olgivie; music, Rudolph Schrager, Leonid Raab.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Brothers -- Drama; Ranchers -- Drama; Western films; Film adaptations; Feature films; Internet videos; Streaming video